COMMUNITY SERVICE TEACHING PRACTICE AS AN EFFORT TO IMPROVE SKILLS AND EXPERIENCE AT THE PRIVATE HIGH SCHOOL OF PEMATANG SIANTAR - Allkando Tampubolon; Antonia Lioncun Br. Sitorus; Silvya Elisya Nainggolan; Helen Natalia Pasaribu; Mastiur Verawaty Silalahi; Masni Veronika Situmorang (RADJA PUBLIKA, 2025)
The Community Service (PKM) Teaching Practice Activity as an Effort to Improve Skills and Experience aims to improve teachers' skills and understanding in compiling scientific papers according to academic principles. This activity is designed to provide the knowledge and skills needed by teachers in the process of writing scientific papers, which is an important aspect in the development of educator professionalism. PPL (Field Experience Practice) is a method of equipping educational students while preparing them to become professional educational personnel. On this occasion I chose to do field experience practice at SMA Swasta Teladan Pematangsiantar which is located at Jl.Singosari No.03 Kel.Bantan, West Siantar, Pematang Siantar. and has been approved by the UHN PPL coordinator to host PPL in 2025. The purpose of the PPL program is to provide opportunities for students to learn about experiencing and living in schools or learning problems related to institutions: improving students' ability to apply knowledge and Field Experience Practice (PPL) which will be completed in February 2025 includes the implementation of guided PPL 1 time. Although there are several challenges, the Field Experience Practice (PPL) Activities at SMA Swasta Teladan Pematangsiantar went smoothly. With the support and direction from various parties, especially the school itself, we were able to overcome the challenges we faced and greatly helped the smooth implementation of the PPL program at the school.